2014
DOI: 10.1016/j.envres.2014.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment׳s insensitive toxicity testing may cause it to fail

Abstract: There are abundant modern experimental methods (and rigorous epidemiology), and an existing systematic review system, to at long last allow academia's toxicity studies to be used in most risk assessments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 83 publications
0
11
1
Order By: Relevance
“…Meanwhile, the EU and ECCC draft databases of chronic toxicity data show neither the same preference for sensitive organisms, nor the distortion in the shape of the SSD over time. These results do not support the notion that industry support of toxicity studies leads to a bias toward publishing insensitive data as was suggested in a recent review (Buonsante et al ). Nevertheless, these results do suggest that legitimate concerns about bias in published toxicity data are warranted.…”
Section: Discussioncontrasting
confidence: 87%
“…Meanwhile, the EU and ECCC draft databases of chronic toxicity data show neither the same preference for sensitive organisms, nor the distortion in the shape of the SSD over time. These results do not support the notion that industry support of toxicity studies leads to a bias toward publishing insensitive data as was suggested in a recent review (Buonsante et al ). Nevertheless, these results do suggest that legitimate concerns about bias in published toxicity data are warranted.…”
Section: Discussioncontrasting
confidence: 87%
“…Compliance with guidelines and Good Laboratory Practice does not guarantee validity and relevance of the study design, statistical rigour and attention to sources of bias. 25 26 The majority of research after the initial marketing approval, including epidemiology studies, will be conducted in research laboratories using various models to address specific issues related to toxicity, often with no testing guidelines available. Peer-reviewed and published findings have great value in understanding mechanisms of carcinogenicity and should be given appropriate weight in an evaluation based on study quality, not just on compliance with guideline rules.…”
Section: Mechanistic Informationmentioning
confidence: 99%
“…The preference for GLP studies has led to marketing authorization dossiers which rely almost exclusively on contract laboratory data provided by the registrants, while excluding peer-reviewed studies from the scientific literature. This has been openly criticized [ 18 ], and several regulatory frameworks [ 1 , 5 , 6 , 8 ] have recently recommended to take all available information into account. This is important since hazard and risk assessments and the derivation of environmental quality criteria (EQC) or standards (EQS) for individual chemicals often suffer from limited data availability.…”
Section: Introductionmentioning
confidence: 99%